2014
DOI: 10.5099/aj140200082
|View full text |Cite
|
Sign up to set email alerts
|

Density-weighted Algorithms for Similarity Computation and Cluster Tree Construction in the RAPD Analysis of Natural Cordyceps sinensis

Abstract: Objective: The goal of this study was to develop and validate density-weighted arithmetic methods for the analysis of the dynamic maturational changes in random amplified polymorphic DNA (RAPD) polymorphisms in Cordyceps sinensis containing multiple fungi. Methods: Ten random primers were used for PCR amplification to monitor changes in the RAPD molecular marker polymorphisms in caterpillar body, stroma and ascocarp portion samples of C. sinensis collected at different stages of maturation. We compared (1) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 18 publications
(65 reference statements)
0
34
0
Order By: Relevance
“…Among these methodologies, RAPD molecular marker polymorphism analysis is the most frequently used technique for comparing overall similarities or dissimilarities (genetic distances) and exploring the phylogenetic (cluster) relationship between the test systems [2,29,[32][33][34][35][36][37][38][39][40][41], although it has been suggested that ISSR may be more sensitive than RAPD [42][43][44] and costly metagenomic approaches may demonstrate advantages in qualitative studies of microbial genetic diversity and molecular ecology [45][46][47]. Among the key factors in study design for molecular marker polymorphism comparisons, the importance of unbiased selection of a plurality of random primers for random amplification of the genomic DNA templates isolated from the examined systems has been addressed [1][2][3][4]40,41]. The use of only a few random primers without reporting the objectivity and representativeness of the selection could lead to bias in the data analysis and thus biased conclusions [1][2][3][4]40,41,48].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these methodologies, RAPD molecular marker polymorphism analysis is the most frequently used technique for comparing overall similarities or dissimilarities (genetic distances) and exploring the phylogenetic (cluster) relationship between the test systems [2,29,[32][33][34][35][36][37][38][39][40][41], although it has been suggested that ISSR may be more sensitive than RAPD [42][43][44] and costly metagenomic approaches may demonstrate advantages in qualitative studies of microbial genetic diversity and molecular ecology [45][46][47]. Among the key factors in study design for molecular marker polymorphism comparisons, the importance of unbiased selection of a plurality of random primers for random amplification of the genomic DNA templates isolated from the examined systems has been addressed [1][2][3][4]40,41]. The use of only a few random primers without reporting the objectivity and representativeness of the selection could lead to bias in the data analysis and thus biased conclusions [1][2][3][4]40,41,48].…”
Section: Introductionmentioning
confidence: 99%
“…The ZUNIX equation (2) defines similarity as the total density of all common parts present in the samples of comparison divided by the total density of all bands across the samples. This algorithm is mathematically general with no specific prerequisites and governs all conditions [40] in contrast to the abundance-unweighted Nei-Li equation (1) [49], which narrows the specific cases under the strict prerequisites (a) and (b) described above. The second ZUNIX equation (3) …”
mentioning
confidence: 99%
See 3 more Smart Citations